Wounding potential of 4.4-mm (.173) caliber steel ball projectiles - Kamphausen, Thomas; Janßen, Katharina; Banaschak, Sibylle; Rothschild, Markus Alexander (International Journal of Legal Medicine, 2019)
From time to time, severe or fatal injuries caused by small caliber air rifle projectiles are seen. In forensic sciences, the theoretical wounding potential of these weapons and projectiles is widely known. Usually, shots against the skull were reported and, in these cases, penetrating the eyes or thin bone layers of the temporal region. Amongst a huge number of different projectiles available for air guns, sub-caliber 4.4-mm (.173) caliber steel ball projectiles were used in an unusual suicide case. This case led to fundamental questions concerning wound ballistics. An 82-year-old man shot once against his right temporal region and twice into his mouth with a 4.5-mm (.177) caliber air rifle. Because of the exceptionally deep penetration of the base of the skull and the use of spherical-shaped sub-caliber air rifle projectiles, terminal ballistic features were analyzed and compared to results published in forensic literature. Test shots using the same weapon and similar projectiles were fired into ballistic gelatin to measure and calculate basic wound ballistic variables of cal. 4.4-mm (.173) steel balls. In comparison, further test shots with cal. 4.5-mm (.177) steel balls BB (ball bearing), flat-headed and pointed air rifle pellets (“diabolos”) were carried out. The theoretical penetration depth in solid bone was calculated with 36.4 mm, and test shots in gelatin from hard contact produced an on-average wound track of 120 mm underlining the potential wounding effect. Furthermore, spherical projectiles could roll back and forth within the barrel, and an air cushion between projectile and breechblock can reduce muzzle velocity by more than half, explaining the retained missile in the temporal region.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Air gun pellet; Ballistics; Gunshot wound; Incapacitation; Penetration depth; Physical activity; Reconstruction